The degree of involvement of the educational leader of teachers in decision-making from the viewpoint of teachers in the Zarqa Directorate (First) of Education - Abo Jhashe, Amal Muner Mohamed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the ability of the educational leader to apply the principle of participation in decision-making and its impact on the achievement of the educational institution’s objectives effectively from the point of view of teachers in the Zarqa Directorate (First) of Education and used the study method descriptive-analytical and the study tool (questionnaire) where it was distributed to a random sample of (110) teachers belonging to the Zarqa Directorate (First) of Education. The study found that the participation of educational leaders in decision-making received an average (2.84 out of 5) verbal (intermediate) ratings, and at the level of fields; Community decision-making average (2.90), teacher participation in decision-making for teachers themselves averaged (2.81) and finally teacher participation in decision-making on the teaching curriculum and teaching methods (2.72), all of which are estimated (2.84), and based on the results, the study recommended the need for teachers to participate in decision-making within educational institutions, which reflects positively on the work of the performance of the institution and improve the type of style possessed by the leader in the institution.